Analisis Pengendalian Kualitas Bibit Sawit Dengan Menggunakan Metode Fault Tree Analysis (FTA) dan Metode Failutre Mode Effect Analysis (FMEA) di PT. Kapuas Sawit Sejahtera - Wahyuniati Ridwan; Retno Widiastuti; Emmy Nurhayati (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Quality is an important factor related to company performance. This quality control is applied in various companies, one of which is PT. Kapuas Sawit, Sejahtera which has a problem with palm seed defects that cannot be overcome. This study aims to identify the factors causing defects in palm seed products. In addition, to provide proposed improvements that can improve the quality of palm seed products. This study uses descriptive qualitative through data analysis of the Fault Tree Analisys (FTA) method and the Failur Mode and Effect Analysis (FMEA) method. Fault Tree Analisys (FTAs). The results of the study through the FTA method obtained the factors causing dwarf defects, defects attacked by diseases, and defects attacked by pests are human, method, and environmental. Through the FMEA method, the proposed improvements made are to carry out cultivation with intensive stature, improve rest time by implementing a short rest system to reduce the impact of the workload, and provide boiler ash before and during the dry season. Researchers hope that the company will further improve the quality of oil palm seeds and that subsequent researchers can develop this research. Keywords: Quality of Oil Palm Seeds, Fault Tree Analisys, Failure Mode and Effect Analysis